2022
DOI: 10.1186/s40900-022-00343-z
|View full text |Cite
|
Sign up to set email alerts
|

A reappraisal of public engagement in Oxford during the pandemic: three case studies

Abstract: Background The COVID-19 pandemic has resulted in the majority of public engagement with research work moving online. This shift to online engagement is likely to affect inclusivity and diversity in such events and this requires further consideration as a result of the pandemic. Through comparing case-studies both pre-dating and during the pandemic, we are able to discern areas for ongoing improvement and learning in the public engagement sphere. Main body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…Social media and virtual platforms . As social media increases in popularity, more studies are using online platforms and virtual means to engage the online public in conversations about genomics 48 , 70 , 71 . Some studies we identified used social media and other virtual platforms simply to invite debate and raise awareness of genomics 48 , 70 , 71 , while others collected data through social media or asked participants to interact with videos or films through a virtual platform 70 , 72 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Social media and virtual platforms . As social media increases in popularity, more studies are using online platforms and virtual means to engage the online public in conversations about genomics 48 , 70 , 71 . Some studies we identified used social media and other virtual platforms simply to invite debate and raise awareness of genomics 48 , 70 , 71 , while others collected data through social media or asked participants to interact with videos or films through a virtual platform 70 , 72 .…”
Section: Resultsmentioning
confidence: 99%
“…As social media increases in popularity, more studies are using online platforms and virtual means to engage the online public in conversations about genomics 48 , 70 , 71 . Some studies we identified used social media and other virtual platforms simply to invite debate and raise awareness of genomics 48 , 70 , 71 , while others collected data through social media or asked participants to interact with videos or films through a virtual platform 70 , 72 . Often, this form of engagement has been used to complement more traditional social sciences research (e.g., surveys, interviews), or traditional forms of engagement (e.g., a panel discussion involving a group of experts, and public audiences invited to attend and ask questions) 70 , 72 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The move to online engagement, necessitated by circumstances, is a learning experience for all involved. However, it is important to note that it is not always inclusive of all the audiences that may want to attend 40 . The size and scale of many of the anatomical structures and the location relative to neighboring structures are often noted by participants attending events.…”
Section: The Recent Landscape Of Anatomical Engagementmentioning
confidence: 99%
“…Over the past couple of years, responses to the covid-19 pandemic has affected possibilities for public involvement in a number of ways, from reducing the likelihood of researchers seeking public involvement to transforming the means through which deliberation occur [55][56][57]. Some of these changes-for instance, the transition to digital methods of involvement-can be enabling for some, but constraining for others, depending upon facility with and access to digital communications.…”
Section: How Do the Exigencies Of The Covid-19 Pandemic Affect The De...mentioning
confidence: 99%